2020
DOI: 10.1177/1060028020932513
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Considerations for CNS Infections Caused by Vancomycin-Resistant Enterococcus faecium: A Focused Review of Linezolid and Daptomycin

Abstract: Objective: To review the current literature describing pharmacology, pharmacokinetics/pharmacodynamics (PK/PD), efficacy, and safety of linezolid and daptomycin for the treatment of central nervous system (CNS) infections caused by vancomycin-resistant Enterococcus (VRE) faecium. Data Sources: A literature search of PubMed/MEDLINE databases was conducted (from 1950 to April 2020) utilizing the following key terms: vancomycin-resistant Enterococcus, VRE, meningitis, ventriculitis, CNS infection, daptomycin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 60 publications
(140 reference statements)
0
25
0
Order By: Relevance
“…After IV infusion of daptomycin 10 mg/kg to patients with meningitis, daptomycin has a minimal penetration into central nervous system (<1% which was corrected to 11.5% after accounting for protein binding). [52,61] By contrast, daptomycin can be an effective treatment option via intrathecal or intraventricular administration when neurosurgical access is available. [52] Distribution into peritoneal fluid.…”
Section: Distribution Within Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…After IV infusion of daptomycin 10 mg/kg to patients with meningitis, daptomycin has a minimal penetration into central nervous system (<1% which was corrected to 11.5% after accounting for protein binding). [52,61] By contrast, daptomycin can be an effective treatment option via intrathecal or intraventricular administration when neurosurgical access is available. [52] Distribution into peritoneal fluid.…”
Section: Distribution Within Central Nervous Systemmentioning
confidence: 99%
“…[52,61] By contrast, daptomycin can be an effective treatment option via intrathecal or intraventricular administration when neurosurgical access is available. [52] Distribution into peritoneal fluid. After IV administration, Gika et al reported good daptomycin distribution within peritoneal fluid, although the ratio between area under the curve (AUC) was not indicated.…”
Section: Distribution Within Central Nervous Systemmentioning
confidence: 99%
“…This is further illustrated by the lack of VREf infection found on autopsy, suggesting that antimicrobial therapy may have been effective at eradicating the pathogen from extravascular tissue where drug concentrations were likely sufficiently high, but not in the CSF. Importantly, to our knowledge this is the first study to report CSF concentrations of oritavancin and tedizolid in humans and one of exceedingly few to measure CSF concentrations of any anti-VREf agent in a patient without an indwelling device such as an extraventricular drain or ventriculoperitoneal shunt [ 5 , 6 , 33 ]. Our work also adds to the currently limited data regarding the in vitro susceptibility of new agents against resistant strains of VREf, specifically eravacycline, omadacycline, and lefamulin [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These difficulties are further augmented when attempting to treat VREf in less pervious body sites, such as the central nervous system (CNS) [ 5 ]. Enterococci are responsible for just 0.3–4% of reported bacterial meningitis cases, with VREf representing exceptionally few of these infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic elements known as van genes confer resistance to Enterococcus of which vanA and vanB present mostly in E. faecium occur the most and are well-distributed, especially among hospital isolates [ 13 ]. There is a disturbing trend following several reports on the resistance of enterococcus to linezolid and daptomycin, two potent antibiotics used against VRE infection [ 14 , 15 ] while Melese et al [ 16 ] stated that the persistent increase in nosocomial infection caused by VRE is being reported by several studies.…”
Section: Introductionmentioning
confidence: 99%